(untitled) (Research, Society and Development, 2022)
Despite being preventable and curable, syphilis is a serious public health problem worldwide. This study seeks to describe the epidemiological and spatial profile of syphilis acquired in the North of Minas Gerais in the years 2016 to 2020. It is a cross-sectional, retrospective and descriptive study. Data collection was carried out using secondary data extracted from the Notification Diseases Information System (SINAN). A descriptive analysis of the variables was performed to characterize the epidemiological profile by checking frequency and percentage. Fisher’s exact statistical test was applied to verify the association of variables, assuming a significance of 95% (p<0.05). The prevalence rate of the historical series studied and the detection rates for each year were calculated and presented in a geospatial illustration for analysis of the geographical and temporal distribution of cases. 1613 notification forms were analyzed, noting a majority male, brown, with complete high school, residing in the urban area, young people between 20 and 29 years old and with evolution towards cure. There were associations between the sex variable and the age group and race variables. The detection rate showed an upward trend between 2016 and 2018, showing a higher concentration of cases in the regional hub. The need to focus on educational health actions is revealed, with the objective of promoting sexual health and offering effective measures to combat syphilis in the most affected population and professional education to qualify the information. It hopes that this study will contribute to propositional strategies and the promotion of similar studies.